2013
DOI: 10.1111/clr.12305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immediate loading on healing of implants installed with different insertion torques – an experimental study in dogs

Abstract: Immediate loading does not seem to have a negative effect on osseointegration. High torque values for the immediate loading procedures were not necessary. Probably, low torque values, were sufficient to obtain primary stability and hence may provide better osseointegration than high torque value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…In another experiment in 6 Labrador dogs including a shorter period of function compared to the previously discussed studies, all mandibular premolars and the first molars were extracted, while the second molars were maintained bilaterally, preserving the distal support in centric occlusion. Two implants were installed 3 months after tooth extraction on both sides of the mandible in the premolar region using insertion torques of about either 30 or >70 Ncm.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In another experiment in 6 Labrador dogs including a shorter period of function compared to the previously discussed studies, all mandibular premolars and the first molars were extracted, while the second molars were maintained bilaterally, preserving the distal support in centric occlusion. Two implants were installed 3 months after tooth extraction on both sides of the mandible in the premolar region using insertion torques of about either 30 or >70 Ncm.…”
Section: Discussionmentioning
confidence: 98%
“…Several experiments evaluating the effect of loading on osseointegration also have been performed in various animal models, such as monkeys, dogs, pigs and rabbits . Some experiments evaluated osseointegration when a physiologic load was applied . Other experiments applied an overload at the test sites, or a non‐axial load or a lateral load …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10] Other authors reported that high insertion torque value is one of the main causes of marginal bone resorption 11 or, however, not necessary. [12][13][14][15] The aim of this article is to review the recent international literature about low and high implant insertion torque investigating their effects on marginal bone loss and implant survival rate.…”
mentioning
confidence: 99%